The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/jee.20130
|View full text |Cite
|
Sign up to set email alerts
|

Creativity as a Factor in Persistence and Academic Achievement of Engineering Undergraduates

Abstract: Background To date, there has been little research to establish how creativity relates to engineering student persistence and academic achievement. Purpose This study used creativity to predict engineering student persistence and achievement relative to demographics, academic aptitude, and personality. It further evaluated those predictors for consistency throughout the undergraduate engineering program. Design/Method Participants were entering first‐year engineering students in 2011 and 2012. Academic aptitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
3
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 40 publications
2
50
3
3
Order By: Relevance
“…Given that some symptoms measured by the ADHD scale are also characteristic of certain normative intellectual styles (i.e., individual differences in the way one approaches tasks and processes information; see Zhang & Sternberg, 2005), the benefits of providing a greater focus on divergent thinking and creativity in engineering education may not be limited to those diagnosed with ADHD. Although engineering GPA was not a significant predictor of divergent thinking in the current study (possibly due to low power), recent research suggests that creativity is not encouraged nor rewarded in traditional engineering programs (e.g., Atwood & Pretz, 2016;Kazerounian & Foley, 2007;Nazzal, 2015).…”
Section: Implications For Engineering Educationcontrasting
confidence: 74%
See 2 more Smart Citations
“…Given that some symptoms measured by the ADHD scale are also characteristic of certain normative intellectual styles (i.e., individual differences in the way one approaches tasks and processes information; see Zhang & Sternberg, 2005), the benefits of providing a greater focus on divergent thinking and creativity in engineering education may not be limited to those diagnosed with ADHD. Although engineering GPA was not a significant predictor of divergent thinking in the current study (possibly due to low power), recent research suggests that creativity is not encouraged nor rewarded in traditional engineering programs (e.g., Atwood & Pretz, 2016;Kazerounian & Foley, 2007;Nazzal, 2015).…”
Section: Implications For Engineering Educationcontrasting
confidence: 74%
“…Traditional, post-secondary engineering education programs, however, do not seem to reward creative efforts (Atwood & Pretz, 2016;Daly, Mosyjowski, & Seifert, 2014;Kazerounian & Foley, 2007). Kazerounian and Foley (2007) found that although 75 surveyed instructors indicated that they valued creativity, over 400 engineering students at the same university believed that their instructors did not actually value creativity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrate a lack of creativity in the engineering curriculum (Atwood &Pretz, 2016;Genco, Holtta-Otto, & Conner Seepersad, 2012;Kazerounian & Foley, 2007).…”
Section: Hypothesismentioning
confidence: 99%
“…Existing metrics of success in academic programs include sixyear graduation (Carey, 2005;Horn, 2006), eight-semester persistence/attrition (Astin & Astin 1992;Lord et al, 2009;Ohland et al, 2008;Seymour & Hewitt, 1997), and integrative multimeasure metrics that rely on a "blending" of more than one measure as a prediction of student success (Alvord, 2004;Kroc, Howard, & Hull, 1997) as examples . Generally speaking, these measures are used to define not only the success of students, but the success of academic departments (Atwood & Pretz, 2016). Despite the wide use of these metrics in the literature for defining student and disciplinary success, these metrics fail to paint the full picture of success within an academic department, including engineering.…”
Section: Introductionmentioning
confidence: 99%